The measurement of labor market entries with SOEP data: Introduction to the variable EINSTIEG_ARTK - Marco Giesselmann; Paul Schmelzer; Mila Staneva; Tobias Wolfram (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
The variable EINSTIEG_ARTK in the file BIOJOB indicates the wave of a first labor market entry. The variable refers to the entry into the labor market after the completion of education and apprenticeship. Since we account for all kinds of employment (full-time, parttime and marginal employment), such a definition captures the uncertainties and instabilities associated with the early career phase. At the same time, side-jobs or apprenticeships are explicitly assigned to the educational phase and excluded from the concept of labor market entry. Among the several plausible concepts and operationalization of labor market entries with SOEP data (among them the "age of first job"-variable), we consequently hold this indicator particularly suited for scholars who want to study the impact of labor market institutions on early career outcomes. As an alternative for researchers who do not rely on exact information on the transitional wave, we offer an alternative variable EINSTIEG_PBIO (that covers more cases, but is only exact on the basis of years, not waves).
Keywords: 330